Factors of employment of graduates of higher educational institutions in Guinea - A. Traore; N. V. Kazantseva (Вестник университета, 2024)
Employment of higher education graduates is a challenge for governments in both developed and developing countries. This article highlights factors that explain the professional integration of graduates leaving universities. This study demonstrates the variables influencing the employment of young tertiary graduates. The model used allows us to establish economic relationships between exogenous and endogenous variables. The variables are qualitative and dichotomous in nature with multiple modalities. The presented results allow us to determine which exogenous variable has a greater impact on the endogenous variable so that governments can consider it in youth employment policies. We also advise young graduates in terms of finding a job. The purpose of this study is to promote the professional integration of Guinean higher education graduates. The main objective is to identify the problems faced in the labour market by Guinean higher education graduates. Using SPSS software, we have obtained the following results: the higher the level of education, the greater the chances of finding a job; personal initiative gives a better chance of finding a job than any other method of finding a job; men have an advantage over women in terms of employment opportunities; married people are luckier than single people; those who have had a previous job are also more likely to find a job than those who have not had; graduates who have lived abroad are more likely to find a job than those who have not lived abroad.